The High Spin Expansion of Twist Sector Dimensions: The Planar 𝒩=4 Super Yang-Mills Theory - Davide Fioravanti; Marco Rossi (Advances in High Energy Physics)
This review is devoted to collecting some results on the high spin expansion of (minimal) anomalous dimension. Thanks to the recent rationale on integrability, planar 𝒩 = 4 super Yang-Mills theory (or its Ad